Using Grammarly to support students’ source-based writing practices - Dong, Yanning; Shi, Ling (Assessing writing, 2021)
To ensure academic integrity, an increasing number of plagiarism detection tools, such as Turnitin, Unicheck, PlagScan, Grammarly, have been developed and adopted at higher education institutions. As plagiarism detection tools are usually used for surveillance and punishment, they may cause anxiety among students without being conducive to students’ learning of source-based writing (Canzonetta, 2019). It is thus worth exploring how plagiarism detection tools work and in which way they can be used positively and effectively to not only provide plagiarism alerts but also help students with their source use practices. In consideration of these purposes, this paper focuses on Grammarly’s plagiarism checker to review its plagiarism detection features and discuss how it can be used as an effective tool to facilitate students’ learning and assessment of source-based writing. Limitations of this tool as well as future considerations are also discussed.